Opportunities And Challenges For Security Education And Training Companies Case Study : PT. Doa Group Indonesia - Deri Yardiansyah; Soleh, Ahmad; Herlina, Yeni (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This research discusses the opportunities and challenges of the PT case study satam education and training company. DOA Group Indonesia. With a qualitative descriptive approach to identify and describe various opportunities owned by PT. DOA Group Indonesia. The data used is secondary, collected from various trusted sources, including scientific journals and official publications from government agencies and related organizations. Big opportunity PT. DOA Group Indonesia is a security guard education and training company in Indonesia because unemployment is still high at the high school/equivalent level, which is the potential for security guard education and training participants. Challenges faced by PT. DOA Group Indonesia is corporate branding, long distance, and many competing companies.